A Review of Distribution Related Problems in Logistics and Supply Chain Research - Xu Yang (International Journal of Supply Chain Management, 2013)
A comprehensive review of distribution problems in logistics and supply chain management is presented in this paper. We first review the definitions of distribution, and then define it from a new perspective. We also present and compare different taxonomies of distribution networks. Next, the importance and difficulties of distribution research are discussed. We point out that there are 12 issues in distribution research that need to be addressed. The major conclusion of the paper is that future research needs to address an integrated approach to distribution design and to consider and incorporate the sustainability development concept.